Grounds for a Christian Statement on Suffering in the Thought of Pope John Paul II - Scerri, Hector (Cultural and religious studies, 2017)
The article seeks to address the problem of suffering in the world by offering a Christian statement on this great issue which has affected and perplexed humanity throughout the ages. The content of the statement is obtained by a presentation of the theme in a wide spectrum of writings and pronouncements made by Pope John Paul II who led the Catholic Church from 1978 to 2005, and who is considered to be one of the most prominent voices regarding human dignity and existential issues in contemporary times. Contemplating the crucified and risen Christ enables Christians to talk about a new meaning to suffering as well as of a "Gospel of suffering". The article enters into themes such as the human predicament when faced with suffering, the mission of those who suffer and solidarity with the suffering.